Optimizing growth and conidia production of Cercospora medicaginis - DJEBALI, Naceur; GAAMOUR, Nahla; BADRI, Mounawer; AOUANI, Mohammed (Phytopathologia Mediterranea, 2010)
The fungus Cercospora medicaginis is pathogenic to annual and perennial Medicago species. It grows slowly and produces only few conidia. To test the pathogenicity or virulence of C. medicaginis and to breed resistant lines of Medicago truncatula we optimized in vitro the growth and the conidium production of four isolates of C. medicaginis derived from M. truncatula and M. polymorpha. Of the eight media tested, that with wheat bran juice (WBJ) yielded optimal growth and conidium production with most strains. The optimum growth temperature on WBJ medium was 25–30°C. Growth and conidia production were better in conditions of alternating light and darkness than with constant darkness. The best growth in the liquid WBJ medium occurred at pH 6–7, but the greatest number of conidia in that medium was obtained at pH 8–9.